MATHEMATICAL MODELS OF EXTREME MODES IN ECOLOGICAL SYSTEMS - Doroshenko, Iryna; Knopov, Oleksandr; Vovk, Liliya (My University, 2022)
The authors consider the basic stages of creating a computer system for decisionmaking support in ecological security. The key factors of environmental pollution caused by ecological and technological catastrophes and typical failures in the operation of hazardous facilities are analyzed. Methods for quantitative estimation of the risk function are proposed. Ecological and mathematical models are created that make it possible to assess the current state of the environment, to make predictions, and provide a comprehension of the process under consideration.
Keywords: model; time series; maximal likelihood method; least squares method; least modules method; minimax method